Efficient Recovery Annealing of the Pseudocapacitive Electrode with a High Loading of Cobalt Oxide Nanoparticles for Hybrid Supercapacitor Applications - Khabibulla A. Abdullin; Maratbek T. Gabdullin; Zhanar K. Kalkozova; Shyryn T. Nurbolat; Mojtaba Mirzaeian (Nanomaterials, 2022)
Electrochemical pseudocapacitors, along with batteries, are the essential components of today’s highly efficient energy storage systems. Cobalt oxide is widely developing for hybrid supercapacitor pseudocapacitance electrode applications due to its wide range of redox reactions, high theoretical capacitance, low cost, and presence of electrical conductivity. In this work, a recovery annealing approach is proposed to modify the electrochemical properties of Co3O4 pseudocapacitive electrodes. Cyclic voltammetry measurements indicate a predominance of surface-controlled redox reactions as a result of recovery annealing. X-ray diffraction, Raman spectra, and XPES results showed that due to the small size of cobalt oxide particles, low-temperature recovery causes the transformation of the Co3O4 nanocrystalline phase into the CoO phase. For the same reason, a rapid reverse transformation of CoO into Co3O4 occurs during in situ oxidation. This recrystallization enhances the electrochemical activity of the surface of nanoparticles, where a high concentration of oxygen vacancies is observed in the resulting Co3O4 phase. Thus, a simple method of modifying nanocrystalline Co3O4 electrodes provides much-improved pseudocapacitance characteristics.